2020
DOI: 10.1055/a-1274-9763
|View full text |Cite
|
Sign up to set email alerts
|

Safety and adequacy of endoscopic ultrasound-guided random liver biopsy in comparison with transjugular and percutaneous approaches

Abstract: Background and study aims Endoscopic ultrasound-guided liver biopsy (EUS-LB) is an accepted technique for tissue acquisition. Traditionally, random LB has been performed with percutaneous (PC-LB) and transjugular (TJ-LB) approaches. The purpose of this study was to compare the safety profile and efficacy of EUS-LB, PC-LB, and TJ-LB. Patients and methods A retrospective analysis was performed at a tertiary academic medical center. Inclusion criteria for analysis were all adult patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
2
8
0
2
Order By: Relevance
“…Recent studies provided discording evidence on the comparative efficacy of EUS-LB as compared to PC-LB to diagnose parenchymal liver disease. In fact, while previous retrospective studies showed similar results between these two approaches [ 15 , 16 , 17 ], a recent small randomized-controlled trial (RCT) suggested better diagnostic performance with PC-LB [ 18 ].…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies provided discording evidence on the comparative efficacy of EUS-LB as compared to PC-LB to diagnose parenchymal liver disease. In fact, while previous retrospective studies showed similar results between these two approaches [ 15 , 16 , 17 ], a recent small randomized-controlled trial (RCT) suggested better diagnostic performance with PC-LB [ 18 ].…”
Section: Introductionmentioning
confidence: 89%
“…There were no statistically significant differences between modalities in regards to rates of adverse events, technical success rate, and diagnostic adequacy. Notably, the number of complete portal tracts for analysis and mean specimen length (two metrics for assessing specimen adequacy) were higher in the EUS-LB group compared to PC-LB and TJ-LB[ 13 ]. These results support comparable safety profile and diagnostic adequacy ( i.e., non-inferiority) of EUS-LB to current standard of care liver biopsy modalities.…”
Section: Liver Biopsymentioning
confidence: 99%
“…Endosonografische und transjuguläre Biopsie sind nur im Einzelfall indiziert zur Abklärung generalisierter Leberparenchymerkrankungen. In der Literatur zeigen die Techniken eine vergleichbare Erfolgsrate [84]. Allerdings finden sich Hinweise auf unterschiedliche Risikoprofile mit etwas höherem Risiko für Blutungen durch perkutane Leberbiopsien und höherem Risiko für kardiale Komplikationen durch transjuguläre Biopsien [85].…”
Section: Leberparenchymerkrankungenunclassified
“…Allerdings finden sich Hinweise auf unterschiedliche Risikoprofile mit etwas höherem Risiko für Blutungen durch perkutane Leberbiopsien und höherem Risiko für kardiale Komplikationen durch transjuguläre Biopsien [85]. Insbesondere unruhige Patienten und Patienten mit eingeschränkter Blutgerinnung können von diesen Alternativen profitieren [84,86,87]. [5,6,112].…”
Section: Leberparenchymerkrankungenunclassified